150 nm × 200 nm Cross‐Point Hexagonal Boron Nitride‐Based Memristors. (16th November 2020) - Yuan, Bin; Liang, Xianhu; Zhong, Liubiao; Shi, Yuanyuan; Palumbo, Felix; Chen, Shaochuan; Hui, Fei; Jing, Xu; Villena, Marco A.; Jiang, Lin; Lanza, Mario
Abstract: The introduction of 2D materials in the structure of memristors has been shown to provide the devices with enhanced flexibility and transparency. However, their use is still not well justified, as the electrical performance of 2D materials‐based memristors is still behind that of transition metal oxide (TMO)‐based memristors. This work presents the fabrication of metal/ h ‐BN/metal memristors with ultra‐low power consumption that beat the previous record set by Au/HfOx :Ag/Au memristors. Moreover, all the methods used to synthesize the 2D materials and fabricate the devices are scalable (e.g., chemical vapor deposition synthesis), and the 2D materials‐based memristors fabricated here use a vertical metal/insulator/metal configuration (i.e., low variability and 3D stackable). To the best of current knowledge, the metal/ h ‐BN/metal memristors here presented are the smallest 2D materials‐based memristors ever reported. Abstract : The introduction of 2D materials in memristors has not been well justified, as the performance of 2D materials‐based memristors is still behind that of transition metal oxide (TMO)‐based memristors. This work presents the fabrication of 150 nm × 200 nm hexagonal boron nitride‐based memristors with ultra‐low power consumption that beat the previous record set by TMO‐based memristors.